On Some Popular Errors Concerning the Scope and Method of Economics – Part 1 - Mises, Ludwig von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
Mises alert to the mistake of confusing Economic History with Economics and maintains that economic history should be interpreted with the help of theories developed by Economics. Explains what reason determines all actions of all men, that is, the removal of any unrest, directly or indirectly and to the greatest extent possible. In seeking this intent men are affected by all the weaknesses and failures of human existence but what determines the real course of events, the price formation and other phenomena called economics, as well as other events of human history, are the thoughts of these fallible men and the effects produced by their actions liable to error. Mises also criticizes the economists’ inability of thinking logically, their abandonment of methodological individualism and the macroeconomic method.